2014
DOI: 10.1617/s11527-014-0492-3
|View full text |Cite
|
Sign up to set email alerts
|

Properties of hot mix asphalt with substituted waste glass

Abstract: In this paper, we studied the properties of hot mix asphalt with substituted waste glass, used for surface layers, made in accordance with standard EN 13108-1. The waste glass was sourced by overcrushing glass from old bottles and broken glass from window frames. We aimed to substitute fractions of individual and cumulative aggregate and fillers in the mineral mixture with glass. We also studied how the compaction in the Marshall's tamper affected the overcrushing of the mineral mixture with the waste glass. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In some EU countries the proportion of recycling has reached as much as 60 %, which is much more compared to situation in the Republic of Croatia where 33,747 tons of waste glass was collected and classified in 2012 [24]. Hand-crushed waste glass used as replacement for a part of filler in the testing is shown in Figure 2 [25]. In the study conducted by Hassan et al [26], glass powder is used as an alternative for mineral filler (stone dust) in the hot asphalt mixture.…”
Section: Use Of Waste Glassmentioning
confidence: 99%
“…In some EU countries the proportion of recycling has reached as much as 60 %, which is much more compared to situation in the Republic of Croatia where 33,747 tons of waste glass was collected and classified in 2012 [24]. Hand-crushed waste glass used as replacement for a part of filler in the testing is shown in Figure 2 [25]. In the study conducted by Hassan et al [26], glass powder is used as an alternative for mineral filler (stone dust) in the hot asphalt mixture.…”
Section: Use Of Waste Glassmentioning
confidence: 99%
“…Ghasemi and Marandi [22] studied the efficiency of bitumen and asphalt mixtures modified with crumb rubber and recycled glass powder, concluding that using recycled glass powder (RGP) instead of crumb rubber (CR) has no negative impact on the efficiency of bitumen and asphalt mixtures and improves their engineering properties, except for the toughness index. Androjić and Dimter [23] replaced some of the aggregates and fillers in the asphalt mix with crushed glass and found that increasing the percentage of glass reduced the density, stability, and void content of the mix. Jin et al [24] used cathode-ray tube glass powders to modify asphalt, and the results revealed that cathoderay tube (CRT) glass powders may be recycled in asphalt binders as an environmentally beneficial recycling technology, with a CRT glass powder addition percentage of up to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, glass waste was one of the materials that was widely used as an alternative for both cement and aggregate in concrete [30][31][32][33][34]. In addition, glass waste was implemented as an eco-alternative to aggregates in asphalt mixtures in most of the flexible pavement layers, especially in the lower, coarser layers [35][36][37]. In addition, some research focused on the replacement of bitumen with glass powder in small ratios up to 10% [38,39].…”
Section: Introductionmentioning
confidence: 99%